The Use of Language Variation in Simalungun Parapat: A Sociolinguistics Study: Array - Sormin, Rizky Khairunnisa (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2021)
Language is a tool of communication that all human use, such as oral/spoken, gesture and written. As a tool for communicating, language has an important role to convey information, intentions, ideas, or opinions in daily life. People in Indonesia do not only use Bahasa Indonesia but they also use the local language or the ethnic language and how those languages are used in daily life and how those languages are placed in certain situations. This study will focus on a variety Simalungun language use in everyday family conversation. This study is a requirement of all to learn and to use language and to enrich the knowledge of the language. When people meet or talk with native speakers of Parapat, not only can they enjoy the meeting and talks but also they can understand Simalungun language. the writer uses qualitative research methods, by collecting and analyzing data related to the topics analyzed. The writer, when collecting data, used interviews, reviewed literature, quoted several related books, the online resources and some related resources. Descriptive analytic method was applied for the selected data and analysis. Based on the analysis why the language use occurs in Simalungun family, that‟s because there is different order of birth with the others in family members, gender between the speaker and the opponent talk, and close relationship with people outside the family member.